Testicular Recovery Effects of Folinic Acid on Cyclophosphamide Induced Damage in Rat - Afsan, Md.; Ahmed, AH Hamid; Khalegue, Md. Abdul; Nessa, Jebum (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Cyclophosphamide is a cytotoxic drug and used as anti-neoplastic agent. It produces gonadal damage leading to infertility. On the other hand Folinic acid is essential in purine synthesis, prevents DNA beak down and essential for spermatogenesis. Therefore, the present study was designed to observe the recovery role of Folinic acid on Cyclophosphamide induced testicular damage. Objective: To observe the recovery effects of Folinic acid on Cyclophosphamide induced testicular damage in Long Evans rats. Methodology: This experimental study was carried out from July 1998 to June 1999 in the Department of Pharmacology, IPGM & R (Under Dhaka University) Dhaka. Twenty four adult Long Evans male rats were pre-treated with Cyclophosphamide, then divided into two groups (A and B).Group of no drug was compared with Folinic acid treated group in 14 day and 28 days. Cytotoxic damage and recovery was assessed by measuring of body weight, testicular weight and volume and the histological findings likely- number of seminiferous tubules, spermatozoa containing tubules, and mean diameter of seminiferous tubules per microscopic field (10X). Serum Testosterone was estimated by Radio Immunoassay to assess if there any Leydig cell damage of rat testes during Cyclophosphamide treatment. Results: After Cyclophosphamide induced toxicity, treatment with Folinic acid produced significant increased in the histological parameters likely- number of seminiferous tubules, spermatozoa containing tubules and mean diameter of seminiferous tubules in 14 days ( p < 0.001) and 28 days (p <0.05). Conclusion: Folinic acid provides significant recovery effects after cyclophosphamide induced gonadal damage in Long Evans rats. J Shaheed Suhrawardy Med Coll, 2011;3 (2): 31-34 DOI: http://dx.doi.org/10.3329/jssmc.v3i2.12074